Blink reflex recovery cycle to differentiate progressive supranuclear palsy from corticobasal syndrome. (12th June 2018) - Sciacca, G.; Nicoletti, A.; Mostile, G.; Luca, A.; Raciti, L.; Dibilio, V.; Drago, F.; Salomone, S.; Zappia, M.
Abstract : Background and purpose: Progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) may share similar clinical findings and tests to distinguish between the two disorders could be useful. We evaluated the blink reflex and R2 blink reflex recovery cycle (R2BRRC), determining diagnostic sensitivity, specificity and positive and negative predictive value of R2BRRC in differentiating patients with PSP from those with CBS. Methods: This was a prospective data collection study investigating blink reflex and R2BRRC at interstimulus intervals (ISIs) of 100, 150, 200, 300, 400, 500 and 750 ms in 12 patients with PSP, eight patients with CBS and 10 controls. Results: Patients with PSP have earlier recruitment of R2BRRC as compared with patients with CBS (ISI: 100 ms, P = 0.002; 150 ms, P < 0.001; 200 ms, P < 0.001; 300 ms, P = 0.02) and controls (ISI: 100 ms, P < 0.001; 150 ms, P < 0.001; 200 ms, P < 0.001; 300 ms, P = 0.004). The presence of an early recovery of the R2 differentiated PSP from CBS with a specificity and sensitivity of 87.5% and 91.7%, respectively. Conclusions: The R2BRRC curve might be considered to be a useful tool in differentiating patients with PSP from those with CBS.